Plant-Derived Natural Products: A Source for Drug Discovery and Development - Noureddine Chaachouay; Lahcen Zidane (Drugs and Drug Candidates, 2024)
For thousands of years, nature has been a source of medical substances, and an astounding numeral of contemporary remedies have been identified from natural origins. Plants have long been used as folk herbal medicines to treat various disorders, and their different natural products have inspired the design, discovery, and development of new drugs. With the invention of recent molecular targets based on proteins, there is a growing need for fresh chemical diversification in screening. Natural products will play a vital part in supplying this need via the continuous exploration of global biodiversity, the majority of which remains unexplored. Even though drug discovery from medicinal plants remains an important source of novel therapeutic leads, various hurdles exist, including identifying and executing suitable high-throughput screening bioassays, scaling up the supply of bioactive molecules, and acquiring plant materials. Investigating these natural resources takes multi-disciplinary, nationwide, and global partnerships in design, synthesis, discovery, and drug development techniques. This review article discusses current advancements and future approaches for discovering natural items such as health- and wellness-promoting remedies. It also summarizes strategies to unify the therapeutic use of plant-derived natural products worldwide to support future drug discoveries derived from plant sources.